The “impaired” or “disabled”: their intrinsic importance in (Christian) society - Dickie, June Frances (Stellenbosch Theological Journal, 2026)
This paper considers the difference between impairment and disability (with the response of others often delineating the difference) and examples of how God often enabled those impaired. The question of somatic healing in prophetic texts (particularly Isaiah and Jeremiah) is discussed in relation to descriptions representing the people’s joy at returning to Zion. The question of whether the texts refer to actual healings or simply metaphors is considered. Attention is also given to how impairment and disability are viewed in the light of growing secular trends. The influence of Darwinism, the rise of “strong men” in society, and some unhelpful theological trends are noted, along with the notion recently broached that God is impaired. This latter concept is shown to be theologically invalid, and it is noted that God does not need to be impaired to care for the impaired.